Advantages of nanofibrous membranes for culturing of primary RPE cells compared to commercial scaffolds - Tichotová, Lucie; Studenovska, Hana; Petrovski, Goran; Popelka, Štěpán; Nemesh, Yaroslav; Sedláčková, Miroslava; Drutovič, Saskia; Rohiwal, Sonali; Jendelová, Pavla; Erceg, Slaven; Brymová, Anna; Artero-Castro, Ana; et al. (Acta ophthalmologica, 2022)
PURPOSE: Dysfunction of the retinal pigment epithelium (RPE) causes numerous forms of retinal degeneration. RPE replacement is a modern option to save vision. We aimed to test the results of transplanting cultured RPEs on biocompatible membranes. METHODS: We cultivated porcine primary RPE cells isolated from cadaver eyes from the slaughterhouse on two types of membranes: commercial polyester scaffolds Transwell (Corning Inc., Kenneburg, ME, USA) with 0.4 µm pore size and prepared Poly (L-lactide-co-DL-lactide) (PDLLA) nanofibrous membranes with an average pore size of 0.4 µm. RESULTS: Five types of assays were used for the analysis: immunocytochemistry (ICC), phagocytosis assay, Western blotting, real-time qPCR (RT-qPCR) and electron microscopy. RT-qPCR demonstrated that RPEs cultured on nanofibrous membranes have higher expressions of BEST1 (bestrophin 1), RLBP1 (retinaldehyde-binding protein 1), RPE65 (retinal pigment epithelium-specific 65 kDa protein), PAX6 (transcription factor PAX6), SOX9 (transcription factor SOX9), DCT (dopachrome tautomerase) and MITF (microphthalmia-associated transcription factor). ICC of the RPEs cultured on nanofibrous membranes showed more intensive staining of markers such as BEST1, MCT1 (monocarboxylate transporter 1), Na+ /K+ ATPase, RPE65 and acetylated tubulin in comparison with commercial ones. Additionally, the absence of α-SMA proved the stability of the RPE polarization state and the absence of epithelial-to-mesenchymal transition. RPE possessed high phagocytic activity. Electron microscopy of both membranes confirmed a confluent layer of RPE cells and their genuine morphological structure, which was comparable to native RPEs. CONCLUSIONS: Retinal pigment epitheliums cultured on polylactide nanofibrous membranes improved the final quality of the cell product by having better maturation and long-term survival of the RPE monolayer compared to those cultured on commercial polyester scaffolds. PDLLA-cultured RPEs are a plausible source for the replacement of non-functioning RPEs during cell therapy.
Keywords: Animals; nanovlákna; eye; Bestrophins; prasata; degenerace retiny; Nanofibers; nanofibrous membrane; kultivované buňky; Polyesters; retinální pigmentový epitel; Cells, Cultured; bestrofiny; Swine; Retinal Pigment Epithelium; AMD; RPE; retina; zvířata; polyestery; Retinal Degeneration; retinal pigment epithelium